Answer:
Explanation:
1). 6x + 7 - 18x + 4
= (6x - 18x) + (7 + 4)
= -12x + 11
2). 5x - 7x + 5x + 4 - 9
= (5x + 5x - 7x) + (4 - 9)
= 3x - 5
3). 3x + 8y - 5x + 3y
= (3x - 5x) + (8y + 3y)
= -2x + 11y
4). 17x² - 7x²- 5x + 3x + 14
= (17x² - 7x²) + (-5x + 3x) + 14
= 10x² - 2x + 14
5). 3xy - 9xy - 5x + 4x - 7 + 3
= (3xy - 9xy) + (-5x + 4x) + (-7 + 3)
= -6xy - x - 4
6). 9x + 7y - 15x + 4x - 9y
= (9x - 15x + 4x) + (7y - 9y)
= -2x - 2y
7). 3x + 7 - 5x - 8y + 4x - 2y + 7
= (3x - 5x + 4x) + (-8y - 2y) + 14
= 2x - 10y + 14
8). 3xy - xy + 15x + 4 - 11
= (3xy - xy) + 15x + (4 - 11)
= 2xy + 15x - 7
9). -8x + 3x + 7y - 5x + 4y - 2
= (-8x - 5x + 3x) + (7y + 4y) - 2
= -10x + 11y - 2
10). 3x² + 6x - 3y + 2x - 7
= 3x² + (6x + 2x) - 3y - 7
= 3x² + 8x - 3y - 7